The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1139/cgj-37-3-638
|View full text |Cite
|
Sign up to set email alerts
|

Shear modulus and damping ratio characteristics of gravelly deposits

Abstract: In this paper, the results of an experimental investigation of dynamic characteristics of gravelly cobble deposits, such as shear modulus (G) and damping ratio (D), are presented. The gravelly cobble deposits are very common in the Taichung metropolitan area of Taiwan where there is an urgent need to determine G and D for dynamic analysis and design of structures. The test program includes measurements of shear wave velocity by the downhole method and large-scale dynamic triaxial tests and resonant-column test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Normalized data points for both materials lie well within the maximum and minimum ranges for gravel soils reported by Seed et al (9). Lin et al and Yasuda and Matsumoto reported similar behavior for gravelly soils (13,14).…”
Section: Dry Specimenssupporting
confidence: 82%
“…Normalized data points for both materials lie well within the maximum and minimum ranges for gravel soils reported by Seed et al (9). Lin et al and Yasuda and Matsumoto reported similar behavior for gravelly soils (13,14).…”
Section: Dry Specimenssupporting
confidence: 82%
“…Seed et al (1986) proposed a set of nonlinear shear modulus reduction and material damping increase curves. Lin et al (2000) used a large-scale cyclic triaxial device with a specimen size of 15 cm (6 in.) in diameter and 30 cm (12 in.)…”
Section: Discussionmentioning
confidence: 99%
“…2.2, for example. Lin et al (2000) performed a test program with measurements of transversal wave velocity by the down-hole method and large-scale dynamic triaxial tests and resonant-column tests of gravely deposit from Taichung area of Taiwan. They found that the shear modulus ratio G/G max of the gravely cobble deposits does not decrease below a value of about 0.5 for shear strain greater than 10 −4 , in contrast to sandy soil.…”
Section: Shear Stiffness and Damping Ratio Dependence On Shear Strainmentioning
confidence: 99%